Home Monitoring System for Comprehensive Geriatric Assessment in Patient's Dwelling: System Design and UX Evaluation - Villalba-Mora, Elena; Ferre, Xavier; Pérez-Rodríguez, Rodrigo; Moral, Cristian; Valdés-Aragonés, Myriam; Sánchez-Sánchez, Alberto; Rodríguez-Mañas, Leocadio (Frontiers in Digital Health, 2021)
Population aging threatens the sustainability of welfare systems since it is not accompanied by an extended healthy and independent period in the last years of life. The Comprehensive Geriatric Assessment (CGA) has been shown to be efficient in maintaining the healthy period at the end of the life. Frailty monitoring is typically carried out for an average period of 6 months in clinical settings, while more regular monitoring could prevent the transition to disability. We present the design process of a system for frailty home monitoring based on an adapted CGA and the rationale behind its User eXperience (UX) design. The resulting home monitoring system consists of two devices based on ultrasound sensors, a weight scale, and a mobile application for managing the devices, administering CGA-related questionnaires, and providing alerts. Older users may encounter barriers in their usage of technology. For this reason, usability and acceptability are critical for health monitoring systems addressed to geriatric patients. In the design of our system, we have followed a user-centered process, involving geriatricians and older frail patients by means of co-creation methods. In the iterative process of design and usability testing, we have identified the most effective way of conducting the home-based CGA, not just by replicating the dialogue between the physician and the patient, but by adapting the design to the possibilities and limitations of mobile health for this segment of users. The usability evaluation, carried out with 14 older adults, has proved the feasibility of users older than 70 effectively using our monitoring system, additionally showing an intention over 80% for using the system. It has also provided some insights and recommendations for the design of mobile health systems for older users.